A reliable algorithm of fourth–order boundary value problems using modified variational iteration method - Rangkuti, Yulita Molliq; Mohd Salmi, Mohd Noorani, Prof. Dr.; Rokiah @ Rozita, Ahmad, Dr. (Universiti Malaysia Perlis (UniMAP), 2010)
1st Regional Conference on Applied and Engineering Mathematics (RCAEM-I) 2010 organized by Universiti Malaysia Perlis (UniMAP) and co-organized by Universiti Sains Malaysia (USM) & Universiti Kebangsaan Malaysia (UKM), 2nd - 3rd June 2010 at Eastern & Oriental Hotel, Penang.